Explainer Videos for Language Learning: A Comparative Study between UiTM and UT - Dianna Suzieanna Mohamad Shah; Ashahri Mohd Salim, Mohamad Safwat; Mohd Salim, Mohd Nur Fitri; Hadianti, Siti; Fauziah, Nurul Isra; Dewi Hartati, Rahma (International Journal of English Language and Pedagogy, 2025)
The integration of explainer videos in language learning has gained significant attention due to their ability to present complex linguistic concepts in a visually engaging and structured manner. This study examines how students from Universiti Teknologi MARA (UiTM) and Universitas Terbuka (UT) engage with explainer videos and compares their effectiveness in enhancing language proficiency. Using a mixed-methods approach, data were collected through questionnaires and open-ended responses from students at both institutions. The findings reveal key patterns in student engagement, preferred video formats, and perceived learning benefits, including improvements in vocabulary acquisition, listening comprehension, and speaking confidence. Differences in institutional learning environments and accessibility also influence student experiences with explainer videos. The study further identifies challenges faced by learners, such as attention span limitations and the need for more interactive elements. Insights from this research contribute to the development of more effective video-based instructional strategies for language learning, catering to diverse student needs across different educational contexts.